2008
DOI: 10.1897/08-009.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of some environmentally relevant parameters on the sorption of polycyclic aromatic hydrocarbons to aqueous suspensions of fullerene

Abstract: Abstract-The wide application of engineered carbon nanomaterials (CNMs), such as fullerene (C 60 ), inevitably will result in their introduction into the aqueous environment. It is likely CNMs will associate with abundant natural organic matter (NOM) and engineered surfactants to form stable aqueous suspensions through various environmental processes. The present study reveals that sorption of polycyclic aromatic hydrocarbons (PAHs) to fullerene resulted in a remarkable decline of freely dissolved PAH concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 39 publications
5
82
0
Order By: Relevance
“…Due to its hydrophobicity, B(a)P absorbs to particulate matter in aqueous environments (Karickhoff, 1984), and TiO2NP, featuring a high surface area could act as adsorption surface for B(a)P. Indeed, previous studies have reported adsorption of PAHs, such as phenanthrene, fluoranthene, and chrysene, to C60 and gold ENPs (Baun et al, 2008;Farkas et al, 2012;Hu et al, 2008). Consequently, by adhesion to aggregating and settling TiO2NP, B(a)P could partly be removed from the water column and hence become less bioavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its hydrophobicity, B(a)P absorbs to particulate matter in aqueous environments (Karickhoff, 1984), and TiO2NP, featuring a high surface area could act as adsorption surface for B(a)P. Indeed, previous studies have reported adsorption of PAHs, such as phenanthrene, fluoranthene, and chrysene, to C60 and gold ENPs (Baun et al, 2008;Farkas et al, 2012;Hu et al, 2008). Consequently, by adhesion to aggregating and settling TiO2NP, B(a)P could partly be removed from the water column and hence become less bioavailable.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of CNMs on the uptake of a compound might thus be better explained via the C free that can be measured with negligible depletion solid-phase microextraction (nd-SPME) (Mayer et al, 2000a,b;Hu et al, 2006;Yang et al, 2008). The C free of polycyclic aromatic hydrocarbons (PAHs) in nC 60 suspensions was measured in our previous study (Hu et al, 2008). The sorption of PAHs to nC 60 resulted in a remarkable decline of their C free , suggesting a reduced diffusive uptake of non-bound HOCs even at relatively low concentrations of nC 60 .…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al reported that aqueous suspensions of fullerene are able to effectively adsorb polycyclic aromatic hydrocarbons (PAHs). This behavior indicates that NPs can affect the solubility of hydrophobic organics contaminants in water [51]. Zero-valent iron nanoparticles represent a promising agent for environmental remediation, and they have been used in several studies as reducing agent to remediate contaminated sites with metals [17,139].…”
Section: Fate Of Nplts In the Environmentmentioning
confidence: 99%